12=-4(6x-3

Simple and best practice solution for 12=-4(6x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12=-4(6x-3 equation:



12=-4(6x-3
We move all terms to the left:
12-(-4(6x-3)=0

See similar equations:

| −5w=7−4w+8 | | 1—4(x−2)+4=12 | | 9(15+x)=297 | | x^2+x-36.4=0 | | 16z−24=8(2z−3) | | -a+28=12 | | n*0.75=36 | | −3t+1=t+9−4t | | 5(2x+4)-4x=32 | | 25=6x-4x+7 | | d=-0.5(0)-10 | | b-26=15 | | 5s=21 | | -1=5p+3p+15 | | 2-v=10 | | 2-|v|=10 | | 3(2x-8)=3x-3 | | 2,5x+18=3.5x-4 | | 6(x=1)-2=2x+4+4x | | -4/5b=27 | | 12x^2-8x-28+21=0 | | k-15/7=12 | | 2(11+x)=46 | | 5x-2(x-4)+8=18 | | -20=4/7*v | | 2(11+x)=54 | | 6/h-25=7 | | 19+5u=99 | | 8x+6x=8x+12 | | -7/8*y=14 | | |3r+6|=18 | | .2x+96=x |

Equations solver categories